Enhancing Business English Conversation Ability by Using Simulation Scenarios for Bachelor Degree Students at North Bangkok University - Sertpunya, Sarinrat; Sukman, Krittat; Nakpathumswat, Prasit (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The objectives of this research were (1) to compare Business English conversation ability by using simulations scenarios for bachelor degree students at North Bangkok University before and after learning by using simulation scenarios, and (2) to assess students’ satisfaction with learning Business English by using simulation scenarios. The sample used in this research consisted of 30 Bachelor Degree of Business Administration Program in Logistics Management and Supply Chain students (Third Years) in the second semester of the 2025 academic year at North Bangkok University selected by using a purposive sampling method. The research instrument used was: (1) Learning management plan for learning Business English conversation by using simulation scenarios; (2) Business English conversation proficiency test; and (3) Student satisfaction assessment form for learning Business English by using simulation scenarios. Statistics used for data analysis included percentage, mean, standard deviation, and t-test. The experiment was conducted using an experimental design by quasi- experimental, one group pre-test – post-test. The research period will be during the second semester of the 2025 academic year, from October 28, 2025 to January 6, 2026, for a total of 10 weeks, with 3 hours per week, amounting to 30 hours. The research results revealed that (1) the Business English conversational ability of bachelor degree students at North Bangkok University after learning by using simulations scenarios was significantly higher than their pre-learning ability at the .05 level. (2) The students were highly satisfied (X = 4.12) with learning Business English using simulations scenarios and the post-test mean scores (21.37) higher than the pre-test score (16.13).